DEVELOPING â€œBATTLESHIPâ€ GAME BASED MATERIAL FOR TEACHING GRAMMAR OF PROCEDURAL TEXT WRITING The Case of The Eighth Grade of Junior High School Students (English Education Journal, 2014)
The problems of this study are ; What games are available to teach grammar for writing procedural text for the eighth grade of Junior High School students?, what games are needed to teach grammar for writing procedural text?, how is the design of Battleship based on grammar for writing procedural text?, how is the Battleship Game implemented to teach grammar for writing procedural text?, and how suitable is the design of Battleship Game to teach grammar for writing procedural text?.Â  This study used Research and Development (R&D). The researcher used the steps proposed by Borg & Gall (Borg & Gall, 1983). Those were used to develop the products and to measure the effectiveness of applying the products. The results of the observation, interview, test, questionnaire, and the expertsâ€™ validations showed that the â€œBattleshipâ€ Game contribute to the process of learning English. Considering the result of the pre test and the post test, it was proven that studying grammar of procedural text by using â€œBattleshipâ€ game will increase Junior High School studentsâ€™ writing skill.